ANALISIS STRATEGI ALIANSI PASOKAN ENERGI LISTRIK PADA SISTEM KELISTRIKAN JAWA BALI YANG DILAKSANAKAN OLEH PT. PLN (PERSERO) PENYALURAN DAN PUSAT PENGATUR BEBAN JAWA BALI - , Sesilia Elfronivantonia Arini ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Java-Bali Transmission and Load Dispatching Center of State Electricity Company (PT PLN (Persero) Penyaluran dan Pusat Pengatur Beban Jawa Bali abbreviated by PLN P3B JB) is become the focus of research because it managed the electricity system in Java and Bali area, with the greatest amount of energy compared to other regions in Indonesia (outside Java and Bali), with an interconnected electricity network. PLN P3B JB transmitting and load dispatching of energy from the electrical energy suppliers (that are power generating companies in Java-Bali) to the retail (that are PLN Distribution units in Java-Bali) and to the specific High Voltage Consumers. In the supply chain system, PLN P3B JB acts as a distributor of electrical energy in Java and Bali region which is the main product of the PLN in general. While power generating companies in the supply chain system that acts as an electrical energy suppliers consists of PLN subsidiaries companies and private investors companies from outside the PLN called IPP (Investor Power Purchase). The study aims to analyze the Porter's Five Forces in order to determine the intensity of the threat of outside parties relating to the alliance